Iatrogenic bladder injuries during obstetric and gynecological surgeries-does it demand prophylactic presence of an urologist? - R., Sankareswari; R., Ghurunaath T.; Shunmugha Sundharam, Ramya Sreevarshni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Iatrogenic bladder injuries (IBI) are more common during obstetric and gynaecological procedures averaging 2.6 IBIs per 1000 surgeries. The objective of the study was to estimate the incidence of IBIs during OBG procedures in a tertiary care hospital at Puducherry. To study the proportion and clinical profile of the IBIs where the management of an urologist was indicated intra-operatively. Methods: This cross-sectional study was conducted in a tertiary care hospital in Puducherry by analysis of records of OBG surgeries conducted during the 5 years’ period from 2011 to 2015. The occurrence of IBIs during obstetric and gynaecological surgeries was estimated and the records of those with injuries were analysed retrospectively. Results: The overall incidence of Iatrogenic Bladder Injuries (IBI) among the OBG surgeries was 1.33% (n=19). Iatrogenic Bladder Injuries (IBI) frequently happened during Gynaecological procedures (73.7%, n=14) than during Obstetric procedures (26.3%, n=5). The incidence of bladder injuries intra-operatively was more frequent during dissection of bladder (57.9%, n=11) and opening the abdomen (36.8%, n=7). The requirement of urologist was more felt during posterior bladder wall injuries (26.3%, n=5). Conclusions: The occurrence of IBIs was more common during Gynaecological procedures than during obstetric procedures. Most of the gynaecological procedures especially hysterectomies require the expertise presence of an urologist.